2017
DOI: 10.1111/cas.13318
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 inhibitors suppress androgen receptor expression in LNCaP95 prostate cancer cells

Abstract: Androgen deprivation therapy is initially effective for treating patients with advanced prostate cancer; however, the prostate cancer gradually becomes resistant to androgen deprivation therapy, which is termed castration‐resistant prostate cancer (CRPC). Androgen receptor splice variant 7 (AR‐V7), one of the causes of CRPC, is correlated with resistance to a new‐generation AR antagonist (enzalutamide) and poor prognosis. Heat shock protein 70 (Hsp70) inhibitor is known to decrease the levels of full‐length AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 37 publications
3
30
0
Order By: Relevance
“…30,31 In LNCaP cells, VER incubation led to a significant activation of caspases over the entire incubation period of 72 hours, as previously shown in lung cancer and melanoma cells. AR, androgen receptor; DMSO, dimethyl sulfoxide; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; PSA, prostate specific antigen; qRT-PCR, real-time quantitative reverse transcription polymerase chain reaction; SD, standard deviation; VER, VER155008 *P < 0.05 nuclear translocation, this might be another explanation besides a potential YB-1-AR interaction described by Kita et al 29 in PCa. This is in line with the description of VER to induce apoptosis in both a caspase-3/7-dependent and -independent manner in different tumors.…”
Section: Discussionmentioning
confidence: 90%
“…30,31 In LNCaP cells, VER incubation led to a significant activation of caspases over the entire incubation period of 72 hours, as previously shown in lung cancer and melanoma cells. AR, androgen receptor; DMSO, dimethyl sulfoxide; GAPDH, glyceraldehyde 3-phosphate dehydrogenase; PSA, prostate specific antigen; qRT-PCR, real-time quantitative reverse transcription polymerase chain reaction; SD, standard deviation; VER, VER155008 *P < 0.05 nuclear translocation, this might be another explanation besides a potential YB-1-AR interaction described by Kita et al 29 in PCa. This is in line with the description of VER to induce apoptosis in both a caspase-3/7-dependent and -independent manner in different tumors.…”
Section: Discussionmentioning
confidence: 90%
“…To help with accuracy, researchers have suggested using the ratio between free to total gama-SM protein level (87). Additionally, studies have shown that Hsp70 can also be used as a co-biomarker for PCa with gama-SM (2, 56, 83). Studies have demonstrated that although Hsp70 has relatively the same level of accuracy of gama-SM in the diagnostics of PCa, it had a far higher level of accuracy in identifying the prognostic and metastatic implications of PCa protein (42, 56).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, studies have shown that Hsp70 can also be used as a co-biomarker for PCa with gama-SM (2, 56, 83). Studies have demonstrated that although Hsp70 has relatively the same level of accuracy of gama-SM in the diagnostics of PCa, it had a far higher level of accuracy in identifying the prognostic and metastatic implications of PCa protein (42, 56). Furthermore, to consolidate, Hsp70 and gama-SM inhibitors have been shown to provide therapeutic relief to PCa cells (82, 83, 88).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations